1134 Protease-Activated Receptor (PAR)-Mediated Contraction of the Chicken Ductus Arteriosus. (October 2012) - Kartal, K; Meekels, J; Mohammed, R; Sterren, S van der; Villamor, E
Abstract : Background and Aims: PARs belong to a family of G protein- coupled receptors, thus mediating the cellular effects of proteinases. PAR1 and PAR2 have been shown to be involved in regulating vascular tone. Thrombin activates PAR1, whereas trypsin activates PAR1 and PAR2. Our aim was to evaluate the functional presence of PAR1 and PAR2 in the ductus arteriosus (DA). Methods: We investigated, using wire myography, the mechanical responses induced by thrombin (0.1 to 3 U/mL), trypsin (0. 1 to 30 U/mL), the PAR1-activating peptide TFLLR- NH2 (1 to 100 µmol/L) and the PAR2-activating peptide SLIGRL-NH2 (0.1 to 10 µmol/L) in DA rings from 15-, 19-, and 21-d chicken embryos. Results: Thrombin, trypsin, and TFLLR- NH2, all caused concentration-dependent contraction of the pulmonary side of chicken DA. These contractions were not observed in the aortic side of the DA, in the femoral artery or in the pulmonary artery. Thrombin-, trypsin- and TFLLR- NH2 -induced contractions were endothelium-independent but markedly impaired by the elimination of calcium from the external medium. The contraction evoked by thrombin and trypsin increased between day 15 and 19 of incubation and was not affected by oxygen tension. SLIGRL-NH2 (≥10 µmol/L), evoked endothelium-dependent relaxation of the DA. Conclusions: PARs are functionally present in the chicken DA but not in other vascular tissues. Recent studies demonstrate that loss of platelet number or function leads to defective DA closure. We speculate that the role of platelets in DA closure might be partially mediated through the PAR-mediated vasoactive effects of thrombin.